Truncated elongation factor G lacking the G domain promotes translocation of the 3' end but not of the anticodon domain of peptidyl-tRNA. - Borowski, C (1996)
The mechanism by which elongation factor G (EF-G) catalyzes the translocation of tRNAs and mRNA on the ribosome is not known. The reaction requires GTP, which is hydrolyzed to GDP. Here we show that EF-G from Escherichia coli lacking the G domain still catalyzed partial translocation in that it promoted the transfer of the 3' end of peptidyl-tRNA to the P site on the 50S ribosomal subunit into a puromycin-reactive state in a slow-turnover reaction. In contrast, it did not bring about translocation on the 30S subunit, since (i) deacylated tRNA was not released from the P site and (ii) the A site remained blocked for aminoacyl-tRNA binding during and after partial translocation. The reaction probably represents the first EF-G-dependent step of translocation that follows the spontaneous formation of the A/P state that is not puromycin-reactive [Moazed, D. & Noller, H. F. (1989) Nature (London) 342, 142-148]. In the complete system--i.e., with intact EF-G and GTP--the 50S phase of translocation is rapidly followed by the 30S phase during which the tRNAs together with the mRNA are shifted on the small ribosomal subunit, and GTP is hydrolyzed. As to the mechanism of EF-G function, the results show that the G domain has an important role, presumably exerted through interactions with other domains of EF-G, in the promotion of translocation on the small ribosomal subunit. The G domain's intramolecular interactions are likely to be modulated by GTP binding and hydrolysis.